Best practice in primary care pathology: review 9. Issue 9 (26th January 2007) - Smellie, W S A; Shaw, N; Bowlees, R; Taylor, A; Howell-Jones, R; McNulty, C A M
Abstract : This ninth best-practice review examines two series of common primary care questions in laboratory medicine: (i) potassium abnormalities and (ii) venous leg ulcer microbiology. The review is presented in question-and-answer format, referenced for each question series. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by MEDLINE EMBASE searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most are consensus rather than evidence-based. They will be updated periodically to take account of new information.